2022
DOI: 10.29374/2527-2179.bjvm001122
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical values in Breton breed horses in Brasília-DF

Abstract: Due to the scarcity of information on Breton horses, the objective was to study hematobiochemical values of this breed. Blood samples were collected from 29 Bretons, males and females, of different ages, in Brasília-DF, distributed into groups, according to age, without distinction of sex (G1): animals from 4 to 9 years old (n=16) and (G2): from 10 to 26 years old (n=13). The horses were also distributed into males and females for comparisons between the sexes. Values for red blood cells, hemoglobin, creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Determination of haematological and biochemical indices of horses’ blood facilitates assessment of their state of health and welfare, nutrient demand, the effects of training already undertaken, and the horses’ suitability for a specific type of exercise ( 5 , 17 ). Blood parameters in the horse are influenced by a number of factors, including the animal’s age, sex, breed, physiological state, reproductive status, regularity, intensity and recentness of physical exercise, and a set of factors that make up the concept of the season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of haematological and biochemical indices of horses’ blood facilitates assessment of their state of health and welfare, nutrient demand, the effects of training already undertaken, and the horses’ suitability for a specific type of exercise ( 5 , 17 ). Blood parameters in the horse are influenced by a number of factors, including the animal’s age, sex, breed, physiological state, reproductive status, regularity, intensity and recentness of physical exercise, and a set of factors that make up the concept of the season.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, analysis of the composition of peripheral blood is an important component of the veterinary examination of horses ( 33 ). Previous studies have shown that haematological parameters and markers of oxidative stress in the blood of horses of different breeds differed significantly ( 1 , 5 ). This may indicate the adaptive reactions in order to maintain homeostasis coming under greater or lesser strain depending on the breed; however, such factors as season and type of exercise may also affect the efficacy of adaptation.…”
Section: Introductionmentioning
confidence: 99%